2019
DOI: 10.1074/jbc.ra119.007356
|View full text |Cite
|
Sign up to set email alerts
|

The antiviral protein viperin regulates chondrogenic differentiation via CXCL10 protein secretion

Abstract: Viperin (also known as radical SAM domain–containing 2 (RSAD2)) is an interferon-inducible and evolutionary conserved protein that participates in the cell's innate immune response against a number of viruses. Viperin mRNA is a substrate for endoribonucleolytic cleavage by RNase mitochondrial RNA processing (MRP) and mutations in the RNase MRP small nucleolar RNA (snoRNA) subunit of the RNase MRP complex cause cartilage-hair hypoplasia (CHH), a human developmental condition characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In addition to the widely studied broad‐spectrum antiviral function of RSAD2 [7–14], emerging evidence suggests the enzyme may play a role in a range of different cellular processes. RSAD2 plays a role in optimal Th2 response [15], regulates thermogenesis in adipose tissue [16], is required for Golgi trafficking of TNF‐α in activated microglia [17], and regulates chondrogenic differentiation via CXCL10 protein secretion [18]. The radical‐SAM activity of RSAD2 can abolish metabolism of amino acids and mitochondrial respiration [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the widely studied broad‐spectrum antiviral function of RSAD2 [7–14], emerging evidence suggests the enzyme may play a role in a range of different cellular processes. RSAD2 plays a role in optimal Th2 response [15], regulates thermogenesis in adipose tissue [16], is required for Golgi trafficking of TNF‐α in activated microglia [17], and regulates chondrogenic differentiation via CXCL10 protein secretion [18]. The radical‐SAM activity of RSAD2 can abolish metabolism of amino acids and mitochondrial respiration [19].…”
Section: Introductionmentioning
confidence: 99%
“…RSV-ARI (n=32) and HC (n=12) samples were used for gene expression analysis using DESeq2 17 , which revealed that 2,878 genes were upregulated and 1,746 genes were down-regulated in RSV-ARI subjects (Figure 5a and Supplementary Table S6). Most of the overexpressed genes are involved in immune response during RSV infection, speci cally interferon response genes, IFIT1, IFIT2, IFIT3, IFI6, and antiviral genes such as IFITM3 18 , IFITM1 19 and MX1 20 , as well as chemokines CCL4, CCL8 and CXCL10 21 . We also identi ed ACOD1 as being signi cantly upregulated in RSV-ARI samples.…”
Section: Resultsmentioning
confidence: 99%
“…All of them are signi cantly expressed in the articular chondrocytes, and Ca2 is mainly localized in the proliferating chondrocytes [44]. Rsad2, also known as viperin, is highly expressed in the middle zone of articular cartilage [45]. Tal1 is a basic helix-loop-helix transcription factor in the articular chondrocytes, and serves as a crucial regulator during chondrocyte maturation [46].…”
Section: Discussionmentioning
confidence: 99%